2005
DOI: 10.1073/pnas.0505256102
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Paneth cell α-defensins in ileal Crohn's disease

Abstract: The pathogenesis of Crohn s disease (CD), an idiopathic inflammatory bowel disease, is attributed, in part, to intestinal bacteria that may initiate and perpetuate mucosal inflammation in genetically susceptible individuals. Paneth cells (PC) are the major source of antimicrobial peptides in the small intestine, including human ␣-defensins HD5 and HD6. We tested the hypothesis that reduced expression of PC ␣-defensins compromises mucosal host defenses and predisposes patients to CD of the ileum. We report that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
818
3
20

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 911 publications
(872 citation statements)
references
References 46 publications
31
818
3
20
Order By: Relevance
“…Paneth cells are the key producers of antimicrobial peptides in the small intestine, such as the α -defensins HD5 and HD6. A study of specimens taken from patients with ileal Crohn ' s disease found that these patients show decreased expression of Paneth cell HD5 and a concomitant reduction in total antimicrobial activity against both E. coli and Staphylococcus aureus ( 33 ). However, a similar decrease in α -defensin production was not seen in patients with Crohn ' s disease of the colon, UC patients, or those with pouchitis.…”
Section: Host Genetic Defects In Containing Commensal Microbiotamentioning
confidence: 89%
“…Paneth cells are the key producers of antimicrobial peptides in the small intestine, such as the α -defensins HD5 and HD6. A study of specimens taken from patients with ileal Crohn ' s disease found that these patients show decreased expression of Paneth cell HD5 and a concomitant reduction in total antimicrobial activity against both E. coli and Staphylococcus aureus ( 33 ). However, a similar decrease in α -defensin production was not seen in patients with Crohn ' s disease of the colon, UC patients, or those with pouchitis.…”
Section: Host Genetic Defects In Containing Commensal Microbiotamentioning
confidence: 89%
“…The present study suggests that HD5 expression coincides with PC development until a GA of 28 wk; in the period starting from 29 wk of GA, HD5 expression increases more rapidly than the number of PCs. PCs with their defensin expression, such as HD5, play a key role in the intestinal innate immunity and development of diseases (13)(14)(15). PCs with their defensin expression are previously described in the pathophysiology of Crohn's disease (15).…”
Section: Discussionmentioning
confidence: 99%
“…Nod2 is highly expressed in Paneth cells of the small intestine [54,55] and Nod2 mutations are associated with ileal location of disease [56] . Studies in humans and mice have shown that normal Nod2 function is required for optimal defensin expression and therefore, impaired defensin expression and regulation may contribute to the increased CD susceptibility observed in Nod2 risk allele carriers [57][58][59] .…”
Section: Nod2 (Card15) Associations To Ileal CDmentioning
confidence: 99%